Host associations and pollution response of ciliate epibionts of macroinvertabrates in six rivers in the Western Cape province of South Africa - Ukumadu NM (2014)
Please help populate SUNScholar with the full text of SU research output. Also - should you need this item urgently, please snd us the details and we will try to get hold of the full text as quick possible. E-mail to scholar@sun.ac.za. Thank you.